Analysis of the Selling Price Determination of Tofu and Tempeh During the COVID-19 Pandemic in Usaha Dagang Solo Asri - Amin Rais; Lusianus Heronimus Sinyo Kelen (Future Science)
Determination of the selling price is important in marketing products, especially during the COVID-19 pandemic which made almost all economic sectors weaken and made business sales, both large and micro, small and medium, to decline. One of the sectors affected by COVID-19 is food production (such as tofu and tempeh businesses). The purpose of this study is to analyze the value or determination of the selling price of tofu and tempeh products during the COVID-19 pandemic. Specifically, data on Usaha Dagang (UD) Solo Asri in the form of costs incurred in one-time production of tofu and tempeh during the COVID-19 pandemic. This business was chosen because it is the largest tofu and tempeh business in Kabupaten Sumba Timur. The method used in analyzing the data in this study is the method of determining the price using cost plus pricing with a full costing approach. The data used in this study is primary data where the researcher conducts direct interviews.This technique was chosen because UD Solo Asri does not have financial reports, so an interview approach is needed to obtain data. From the results of data processing, it can be concluded that the selling price for each product with an expected profit of 10 percent during the COVID-19 pandemic is Rp275 per 3 pieces for tofu and RP7.476 per 7 packs of tempeh.